Double cortical line in the acetabular roof of paraplegic patients - Dai, L; Hou, C (Chinese medical journal, 1995)
The pelvic radiographs of 60 patients with paraplegia or quadriplegia were reviewed and double cortical line in the acetabular roofs on both sides was found in 35 patients. It was concluded that the double cortical line was a radiologic sign of disuse osteoporosis after spinal cord injury. It was noticed that the acetabular double cortical line in incomplete paralysis was not so prominent as that in complete paralysis (P < 0.05), suggesting that the degree of acetabular osteoporosis may be related to the severity of spinal cord injuries. The etiology of double cortical line and related factors were discussed.